Dinámicas sociales y económicas dadas por el proceso de conurbación del municipio de Cota, Cundinamarca, Colombia (2020)
The phenomenon of conurbation that has affected the municipality of Cota (Cundinamarca, Colombia) has led to new social and economic dynamics in the region, causing changes in the activities that were carried out there. A phenomenon of high migration of native inhabitants of the municipality, change of economic activities, and high competition for land use, leaving out the primary sector of the economy, by favoring in the first instance the new activities coming from the city of Bogota. A study was carried out to clearly visualize how the phenomenon changed traditions and directly affected families that depended on agricul-tural activities.